Civil and Criminal Liability for Committing Genocide - Falhi, Haifa (Journal of Legal Sciences, 2026)
Genocide is a crime known to humanity, and its commission increased, particularly during the First and Second World Wars. Therefore, the first court was established to try perpetrators of crimes against humanity, with the Nuremberg Tribunal. The tribunal defined international crimes such as murder, enslavement, extermination, deportation, and any acts against civilian populations before and during the war. It also defined persecution based on political, racial, or religious grounds, when such oppressive acts constitute a crime against peace or a war crime in connection with such acts. Therefore, the issue of genocide has captured the attention of jurists and legal scholars, and the international community has sought to take measures to limit and prevent these international crimes. This has been achieved by seeking international legal cover to criminalize and punish these acts. This was achieved through the conclusion of the Convention on the Prevention and Punishment of the Crime of Genocide in 1948. However, genocide continues despite the existence of the Convention, demonstrating the shortcomings of the legal system for preventing the crime of genocide at the international and national levels, in terms of establishing appropriate mechanisms to comply with the provisions of the Genocide Convention.